2014
DOI: 10.3892/etm.2014.1755
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width predicts short- and long-term outcomes of acute congestive heart failure more effectively than hemoglobin

Abstract: The present study compared short- and long-term prognostic values of red blood cell distribution width (RDW) with those of hemoglobin (Hgb) among patients with acute congestive heart failure (CHF) in a cardiac care unit. The cross-sectional study examined data from 521 patients with acute CHF who were admitted to a cardiac care unit and followed up for 24 months (median). Mean Hgb levels in patients who succumbed (DIH) or remained alive (AIH) were 11.0±1.8 and 11.8±2.6 g/l (P>0.05), respectively. Median values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
16
1
2
Order By: Relevance
“…In the average adult, 200 billion red blood cells (RBCs) are generated daily from hematopoietic stem cells in the bone marrow. The most commonly assessed traits for mature RBCs are hematocrit (HCT), hemoglobin concentration (HGB), mean corpuscular hemoglobin (MCH), MCH concentration (MCHC), mean corpuscular volume (MCV), RBC count (RBCC), and red cell distribution width (RDW); together, these traits are used to characterize RBC development and function, diagnose anemic disorders, and identify risk factors for complex chronic diseases [1][2][3][4][5][6]. RBC traits also are moderately to highly heritable, making these complex quantitative traits excellent candidates for genomic interrogation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the average adult, 200 billion red blood cells (RBCs) are generated daily from hematopoietic stem cells in the bone marrow. The most commonly assessed traits for mature RBCs are hematocrit (HCT), hemoglobin concentration (HGB), mean corpuscular hemoglobin (MCH), MCH concentration (MCHC), mean corpuscular volume (MCV), RBC count (RBCC), and red cell distribution width (RDW); together, these traits are used to characterize RBC development and function, diagnose anemic disorders, and identify risk factors for complex chronic diseases [1][2][3][4][5][6]. RBC traits also are moderately to highly heritable, making these complex quantitative traits excellent candidates for genomic interrogation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Una serie de estudios han demostrado que el RDW predice en forma significativa la presencia y severidad de ECV en pacientes con IC [17][18][19] , infarto agudo al miocardio (IAM) previo [20][21][22] y fibrilación auricular 23 . En relación a la IC, diversos estudios desde el publicado por Felker y cols., han mostrado una relación positiva entre el RDW y diferentes pará-metros como grado funcional de la NYHA 17 , readmisiones hospitalarias 18 , y péptido natriurético tipo B (BNP) 19 .…”
Section: Rdw Como Predictor De Morbilidad Cardiovascularunclassified
“…En relación a la IC, diversos estudios desde el publicado por Felker y cols., han mostrado una relación positiva entre el RDW y diferentes pará-metros como grado funcional de la NYHA 17 , readmisiones hospitalarias 18 , y péptido natriurético tipo B (BNP) 19 . En relación a este último marcador sanguíneo altamente estudiado en la IC, se ha reportado una robusta asociación entre el aumento del RDW y el BNP.…”
Section: Rdw Como Predictor De Morbilidad Cardiovascularunclassified
“…Among them, red cell distribution width (RDW) was found to be the cheapest and most widely available indicator. The RDW was established to be a strong predictor of mortality in the general population above 45 years of age [2], as well as during sepsis, trauma and in critically ill patients [3][4][5]. Several studies confirmed that RDW predicts mortality in acute and chronic heart failure (CHF) [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The RDW was established to be a strong predictor of mortality in the general population above 45 years of age [2], as well as during sepsis, trauma and in critically ill patients [3][4][5]. Several studies confirmed that RDW predicts mortality in acute and chronic heart failure (CHF) [5][6][7][8][9]. It was reported that an increasing RDW value is associated with cytokine activation, impaired iron mobilization and decreased hemoglobin (Hb) levels [10][11][12].…”
Section: Introductionmentioning
confidence: 99%